2014
DOI: 10.1111/hiv.12122
|View full text |Cite
|
Sign up to set email alerts
|

Community HIV‐1 drug resistance is associated with transmitted drug resistance

Abstract: Objective Since community viral load (CVL) measurements are associated with incidence of new HIV-1 infections in a population, we hypothesized that similarly measured community drug resistance (CDR) could predict prevalence of transmitted drug resistance (TDR). Methods Between 2001 and 2011, the prevalence of HIV-1 drug resistance for patients with established infection receiving HIV care (i.e. CDR) and TDR in recently infected patients was determined in San Diego. At each position in HIV-1 reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Twenty-five clusters (18.1%) had two or more individuals sharing one or more drug resistance mutations, accounting for 78.0% of the clustering individuals with resistance. The most common drug resistance mutation was K103N, which was represented in 11.5% of entire cohort and 10.9% of clustering individuals, and is similar to the prevalence of K103N seen in newly infected individuals in San Diego ( Tilghman et al, 2014 ).…”
Section: Resultssupporting
confidence: 56%
“…Twenty-five clusters (18.1%) had two or more individuals sharing one or more drug resistance mutations, accounting for 78.0% of the clustering individuals with resistance. The most common drug resistance mutation was K103N, which was represented in 11.5% of entire cohort and 10.9% of clustering individuals, and is similar to the prevalence of K103N seen in newly infected individuals in San Diego ( Tilghman et al, 2014 ).…”
Section: Resultssupporting
confidence: 56%
“…Clinicians should then switch treatment. Delaying treatment switching leads to accumulation of resistance mutations [3][4][5], unfavourable patient outcomes and increased risk of transmission of drug-resistant strains [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. If the second consecutive VL is re-suppressed, patients usually remain on the same treatment regimen assuming that treatment adherence is restored without major drug resistance (DR).…”
Section: Introductionmentioning
confidence: 99%
“…These categories of resistance may provide an indication of how well a city is maintaining treatment and adherence in its infected population. Additionally, Tilghman et al found that high levels of CDR at specific gene locations predicted TDR in the same locations [ 33 ].…”
Section: Introductionmentioning
confidence: 99%